The Effect of the 3D Nanoarchitecture and Ni‐Promotion on the Hydrogen Evolution Reaction in MoS2/Reduced GO Aerogel Hybrid Microspheres Produced by a Simple One‐Pot Electrospraying Procedure. Issue 14 (6th March 2022) - Ran, Jiajia; Girardi, Leonardo; Dražić, Goran; Wang, Zhanhua; Agnoli, Stefano; Xia, Hesheng; Granozzi, Gaetano
Abstract: The transition toward renewable energy sources requires low‐cost, efficient, and durable electrocatalysts for green H2 production. Herein, an easy and highly scalable method to prepare MoS2 nanoparticles embedded in 3D partially reduced (pr) graphene oxide (GO) aerogel microspheres (MoS2 /prGOAMs) with controlled morphology and composition is described. Given their peculiar center‐diverging mesoporous structure, which allows easy access to the active sites and optimal mass transport, and their efficient electron transfer facilitated by the intimate contact between the MoS2 and the 3D connected highly conductive pr‐GO sheets, these materials exhibit a remarkable electrocatalytic activity in the hydrogen evolution reaction (HER). Ni atoms, either as single Ni atoms or NiO aggregates are then introduced in the MoS2 /prGOAMs hybrids, to facilitate water dissociation, which is the slowest step in alkaline HER, producing a bifunctional catalyst. After optimization, Ni‐promoted MoS2 /prGOAMs obtained at 500 °C reach a remarkable η10 (overpotential at 10 mA cm −2 ) of 160 mV in 1 m KOH and 174 mV in 0.5 m H2 SO4 . Moreover, after chronopotentiometry tests (15 h) at a current density of 10 mA cm −2, the η10 value improves to 147 mV in alkaline conditions, indicating an exceptional stability. Abstract : Ni‐promoted MoS2 nanoparticles embedded in 3D reduced graphene oxide aerogel microspheres are fabricated through a simple, high‐throughput electrospraying‐based procedure. Given their center diverging microchannel morphology which allows fast electron and electrolyte transport, the microspheres have excellent electrochemical performances in the hydrogen evolution reaction, which is further boosted in alkaline conditions by the Ni species able to assist water dissociation.